Alexithymia and depression in patients with fibromyalgia: When the whole is greater than the sum of its parts. (September 2017) - Ghiggia, Ada; Romeo, Annunziata; Tesio, Valentina; Tella, Marialaura Di; Colonna, Fabrizio; Geminiani, Giuliano Carlo; Fusaro, Enrico; Castelli, Lorys
Abstract: This study investigated the link between alexithymia and depressive symptoms in Fibromyalgia (FM). 181 FM women and 181 healthy controls (HC) were compared using the Hospital Anxiety and Depression Scale and the Toronto Alexithymia Scale. A moderation analysis was performed to examine the moderation effect of the group (FM vs. HC) on the relationship between alexithymia and depression. Group was a significant moderator, highlighting a stronger relationship between alexithymia and depressive symptoms in the FM compared to HC. The study highlighted that the association between alexithymia and depression is different when we consider FM patients rather than the healthy population. Highlights: The relationship between alexithymia and depression was studied in a large FM sample. FM patients showed a significantly higher presence of alexithymia and depression. Results showed a stronger relationship between alexithymia and depression in FM.